THE DEGREE OF STUDENTS INVOLVEMENT IN THE SOCIAL STUDIES TEXTBOOK FOR SIX INTERMEDIATE BASIC SCHOOL IN KURDISTAN REGION ’STUDY AND ANALYSIS’ - HAJİ, Sattar Jabbar (The Eurasia Proceedings of Educational and Social Sciences, 2016)
The current study aimed to investigate the degree of students' involvement in the social studies textbook for Six Intermediate Basic School in the Kurdistan Region by it is three units: Geography, History, Citizenship, through the presentation of: educational content, Figures & diagrams, and educational activities. The study also aimed to investigate the difference in the degree of students' involvement in the textbook according to educational units. To achieve this aim the researcher utilized Romy's method to calculate the variables of students' involvement coefficients, and Chi-square test to investigate the differences in involvement degree of the textbook according to educational units. The results showed revealed reduction of students' involvement in educational content in geography, history, Citizenship units, and did not located within the acceptable range adopted by Romy's, it is values were (0.06, 0.10, 0.13) consecutively, the results also showed revealed reduction involvement in figures & diagrams in geography unit it is value reached (0.12), and non- involvement for history and citizenship, and the students' involvement through educational activities the book showed an excellent student except in geography unit with coefficient (0.31). The results also revealed that there were no statistical significant differences in the level (0.05) in each educational content and activities, with statistically significant differences at the significance level (0.05) in the figures & diagrams. The researcher recommended the need for much attention to the students involvement in social studies textbook in educational content, figures & diagrams, and activities in geography unit, moreover, doing further typical analytical studies to be conducted on social studies textbooks in other classrooms in general, in the light of the degree of the student involvement in it.